An international survey of chronic obstructive pulmonary disease in young adults according to GOLD stages. Issue 2 (3rd February 2004) - de Marco, R; Accordini, S; Cerveri, I; Corsico, A; Sunyer, J; Neukirch, F; Künzli, N; Leynaert, B; Janson, C; Gislason, T; Vermeire, P; Svanes, C; et al.
Abstract : Background: The recently published GOLD guidelines provide a new system for staging chronic obstructive pulmonary disease (COPD) from mild (stage I) to very severe (stage IV) and introduce a stage 0 (chronic cough and phlegm without airflow obstruction) that includes subjects "at risk" of developing the disease. Methods: In order to assess the prevalence of GOLD stages of COPD in high income countries and to evaluate their association with the known risk factors for airflow obstruction, data from the European Community Respiratory Health Survey on more than 18 000 young adults (20–44 years) were analysed. Results: The overall prevalence was 11.8% (95% CI 11.3 to 12.3) for stage 0, 2.5% (95% CI 2.2 to 2.7) for stage I, and 1.1% (95% CI 1.0 to 1.3) for stages II–III. Moderate to heavy smoking (⩾15 pack years) was significantly associated with both stage 0 (relative risk ratio (RRR) = 4.15; 95% CI 3.55 to 4.84) and stages I+ (RRR = 4.09; 95% CI 3.17 to 5.26), while subjects with stages I+ COPD had a higher likelihood of giving up smoking (RRR = 1.39; 95% CI 1.04 to 1.86) than those with GOLD stage 0 (RRR = 1.05; 95% CI 0.86 to 1.27). Environmental tobacco smoke had the same degree of positive association in both groups. Respiratory infections in childhood and low socioeconomic class were significantly and homogeneously associated with both groups, whereas occupational exposure was significantly associated only with stage 0. All the GOLD stages showed a significantly higher percentage of healthcare resource users than healthy subjects (p<0.001), with no difference between stage 0 and COPD. Conclusions: A considerable percentage of young adults already suffered from COPD. GOLD stage 0 was characterised by the presence of the same risk factors as COPD and by the same high demand for medical assistance.